Efikasi Diri dan Sikap Perawat dalam Melaporkan Insiden Keselamatan Pasien di Rumah Sakit - Zakiyyah, Naadiyah; Handiyani, Hanny; Hariyati, Rr. Tutik Sri; Novieastari, Enie (Universitas Malahayati, 2024)
ABSTRACT Nurses' negative attitudes in reporting patient safety incidents has an impact on the low number of reported incidents (underreporting). Reporting incidents is beneficial and can be a lesson to prevent the recurrence of similar incidents so it’s improve patient safety. Self-efficacy is a factor that encourages nurses to have a positive attitude towards reporting incidents. Efficacy is an individual's belief in their ability to overcome a particular task. This research aims to identify the relationship between self-efficacy and nurses' attitudes in reporting patient safety incidents in hospitals. This cross-sectional study involved 117 nurses selected using probability sampling. The study used the Reporting of Clinical Adverse Events (RoCAES) questionnaire and the General Self Efficacy (GSE) questionnaire. The results shows that there is a strong relationship between nurse’s self-efficacy and nurses' attitudes in reporting patient safety incidents (p= 0.001). High self-efficacy improves nurses' attitudes towards reporting incidents. Recommendations for hospitals to establish clear procedures regarding the types of incidents that must be reported, create a climate of no blame and shame, and promote nurses' self-efficacy by regularly holding training and sharing knowledge and experience in reporting patient safety incidents. Keywords: Attitude; Nurse; Patient Safety Incident; Self-Efficacy ABSTRAK Masalah sikap perawat yang negatif dalam melaporkan insiden berdampak pada rendahnya angka insiden yang dilaporkan (underreporting). Pelaporan insiden bermanfaat sebagai pembelajaran untuk mencegah terulangnya kejadian serupa sehingga dapat meningkatkan keselamatan pasien. Efikasi diri merupakan faktor yang mendorong perawat untuk bersikap positif terhadap pelaporan insiden. Efikasi merupakan keyakinan individu terhadap kemampuan yang dimiliki dalam mengatasi suatu tugas tertentu. Penelitian ini bertujuan untuk mengidentifikasi hubungan efikasi diri dan sikap perawat dalam melaporkan insiden keselamatan pasien di rumah sakit. Penelitian cross-sectional ini melibatkan 117 perawat yang dipilih secara probability sampling. Penelitian menggunakan kuesioner Reporting of Clinical Adverse Events (RoCAES) dan kuesioner General Self Efficacy (GSE). Hasil didapatkan adanya hubungan yang kuat antara efikasi diri perawat dan sikap perawat dalam melaporkan insiden keselamatan pasien (p= 0,001). Efikasi diri yang tinggi meningkatkan sikap perawat terhadap pelaporan insiden. Rekomendasi bagi pihak rumah sakit untuk menetapkan prosedur yang jelas terkait jenis insiden yang harus dilaporkan, menciptakan iklim tidak menyalahkan dan memalukan, dan meningkatkan potensi efikasi diri perawat dengan rutin mengadakan pelatihan dan berbagi ilmu serta pengalaman dalam melaporkan insiden. Kata Kunci: Efikasi Diri; Insiden Keselamatan Pasien; Perawat; Sikap